Enhancing control of highly pathogenic avian influenza in developing countries through compensation: issues and good practice: executive summary - Delgado, Christopher L.; Mckenzie, Patricia; de Haan, Cornelis; Mcleod, Anni; Rivieve-Cinnamond, Ana; Narrod, Clare (World Bank, 2006)
This is the executive summary of a report drafted by an interdisciplinary and interagency task team led by Christopher Delgado of the Agriculture and Rural Development Department of the World Bank, involving staff and consultants from the World Bank, the Food and Agriculture Organization (FAO), and the International Food Policy Research Institute (IFPRI). The core drafting team, which accepts responsibility for the views expressed in the report, consisted of Christopher Delgado, Patricia McKenzie, and Cornelis de Haan (World Bank); Anni McLeod and Ana Riviere-Cinnamond (FAO); and Clare Narrod (IFPRI). Funding was provided by the Operations Policy and Country Services and the Agricultural and Rural Development Departments of the World Bank, and by FAO, IFPRI, and the World Animal Health Organization (OIE).